2020
DOI: 10.1177/0741932520964918
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Single-Case Research on Word-Problem Instruction for Students With Learning Disabilities

Abstract: In this meta-analysis of single-case designs, the researchers investigated the effects of word-problem instruction for students with learning disabilities in Grades 1 through 12, as reported in 20 peer-reviewed articles published between 1975 and 2020. A two-level multilevel model with a robust variance estimation method was implemented to calculate the effect sizes. A significant overall effect of word-problem instruction for students with learning disabilities was found, and the results indicate that studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
(169 reference statements)
0
15
0
Order By: Relevance
“…Because these two mathematics topics have consistently been a building block for successful mathematics in elementary and secondary mathematics (National Center for Education Statistics, 2019 ), it is assumed that researchers have been trying to investigate how to tackle these mathematical difficulties. Furthermore, since the release of the National Mathematics Advisory Panel’s report ( 2008 ) on highlighting the importance of teaching fractions as being a critical foundation of algebra and emphasizing students’ conceptual knowledge for understanding and solving mathematical word problems across topics, there have been an increasing number of intervention and review studies (Ennis & Losinki, 2019 ; Morano et al, 2020 ; Shin et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Because these two mathematics topics have consistently been a building block for successful mathematics in elementary and secondary mathematics (National Center for Education Statistics, 2019 ), it is assumed that researchers have been trying to investigate how to tackle these mathematical difficulties. Furthermore, since the release of the National Mathematics Advisory Panel’s report ( 2008 ) on highlighting the importance of teaching fractions as being a critical foundation of algebra and emphasizing students’ conceptual knowledge for understanding and solving mathematical word problems across topics, there have been an increasing number of intervention and review studies (Ennis & Losinki, 2019 ; Morano et al, 2020 ; Shin et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Methods used to detect asymmetry and publication bias are routinely employed in meta-analyses of group-design research. Although used less often in behavior analysis research compared to other fields, these methods are used in metaanalyses of behavioral research (see e.g., Amlung et al, 2016;McCormack et al, 2019) and meta-analyses of SCED studies (see e.g., Babb et al, 2020;Bowman-Perrot et al, 2014;Garwood et al, 2021;Shin et al, 2020). When attempting to aggregate behavior science research using frequentist statistical analysis, heterogeneity should be accounted for in the model minimally at the participant level (level 1) and the study level (level 2), referred to as a multilevellevel model meta-analysis (Becraft et al, 2020;Moeyaert et al, 2020).…”
Section: Meta-analytic Publication Bias Methods and Behavior Sciencementioning
confidence: 99%
“…Ledford and Gast (2018) suggested that moderator analysis logic in SCED research could help uncover the boundaries of treatment. For example, Shin et al (2020) conducted a meta-analysis to evaluate the effects of word problem solving interventions for students with a learning disability that used single-case research design. The authors used meta-regression to investigate multiple variables of interest (i.e., study quality, content domain of word problems, mathematical practice standards embedded in intervention) and identified whether effects varied.…”
Section: Benefits Of Meta-analyses In Appliedmentioning
confidence: 99%